2018
DOI: 10.14738/assrj.55.4233
|View full text |Cite
|
Sign up to set email alerts
|

Bloom Taxonomy Of Educational Objectives And The Modification Of Cognitive Levels

Abstract: The author is of the opinion that the Bloom taxonomy of educational objectives particularly the six cognitive levels should reflect the levels of cognitive development and thinking of students. This thinking pattern would no doubt, reflect the student's environment and his genetic composition. In the light of this, Bloom's cognitive levels should not be generalised and it would be better if the six levels are collapsed into low, Medium and high cognitive process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…The first stage of the simulation, named preparation, is divided into pre-simulation and pre-briefing/briefing. In both, the actions that must be approached to develop knowledge are knowing and understanding (21) .…”
Section: Discussionmentioning
confidence: 99%
“…The first stage of the simulation, named preparation, is divided into pre-simulation and pre-briefing/briefing. In both, the actions that must be approached to develop knowledge are knowing and understanding (21) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the intended learning outcomes of the course were designed and classified in accordance with the cognitive domain of the Bloom's taxonomy of educational objectives, which has been amended by Krathwohl and Anderson [26]. Special emphasis was placed on promoting knowledge, gratifying curiosity, broadening views, and strengthening wisdom and judgement among students [1,3,7,19,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…According to these theories, students learn as a result of internal processes in which higher-order mental activities including memory, perception, thinking, problem-solving, reasoning, and concept formation take place [30]. Cognitive learning theories proposed that learning is a result of interactions between new information acquired by an individual and the existing information, specifically, when relevant structured are already existent [26,31]. The use of Bloom's verbs in this study might ensure targeting the lower and upper orders of the cognitive domain.…”
Section: Discussionmentioning
confidence: 99%
“…Exam format can also have a differential impact on students as many studies have demonstrated that males tend to perform better on restricted response questions and women tend to perform better on constructed response questions (mazzeo, Schmitt and Bleistein, 1993). one way of evaluating the cognitive level of exams and their question is to categorise each question according to bloom's taxonomy of cognitive domains (Adesoji, 2018). learning taxonomies or classification are commonly used as a way of describing different kinds of learning behaviour and characteristics.…”
Section: Introductionmentioning
confidence: 99%